Proceeding of the Thirteenth International Symposium on Low Power Electronics and Design - ISLPED '08 2008
DOI: 10.1145/1393921.1393937
|View full text |Cite
|
Sign up to set email alerts
|

A parallel and randomized algorithm for large-scale discrete dual-Vt assignment and continuous gate sizing

Abstract: We propose a parallel and randomized algorithm to solve the problem of discrete dual-Vt assignment combined with continuous gate sizing which is an important low power design technique in high performance domains. This combinatorial optimization problem is particularly difficult to solve on large-sized circuits. We first introduce a hybrid algorithm which combines the existing heuristics and convex formulations for this problem to achieve a better tradeoff between the runtime of the algorithm and the quality o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…When leakage power becomes prominent, people start to use gates with different threshold voltage (V t ) levels in order to trade timing slack for leakage power reduction [6][7][8]. Due to the similarity between them, gate/transistor sizing and V t assignment are often conducted simultaneously [9][10][11][12][13][14]. Among these previous works, [6] and [12] are greedy or sensitivity driven heuristics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When leakage power becomes prominent, people start to use gates with different threshold voltage (V t ) levels in order to trade timing slack for leakage power reduction [6][7][8]. Due to the similarity between them, gate/transistor sizing and V t assignment are often conducted simultaneously [9][10][11][12][13][14]. Among these previous works, [6] and [12] are greedy or sensitivity driven heuristics.…”
Section: Introductionmentioning
confidence: 99%
“…In [7,13], continuous optimization is performed and then the results are rounded to obtain discrete solutions. The work of [14] exploits parallelism in discrete V t assignment and continuous gate sizing. In [11], it is found that linear programming based optimization often results in discrete V t assignment solutions and therefore the rounding can be skipped.…”
Section: Introductionmentioning
confidence: 99%
“…However, it will result in the significant degradation of circuit delay compared to the obtained continuous gate sizing solution [56,58]. This motivates some recent works to design combinatorial algorithms which directly handle discrete gate size, such as a continuous solution guided dynamic programming technique in [56], a network-flow based approach in [59], a parallelization and randomization based technique in [60], and a multi-dimensional gradient descent based algorithm in [61]. These algorithms are effective, however, they are all heuristics without any theoretical guarantee on the quality of their discrete gate sizing solutions.…”
Section: Sizing Targeting Delay Minimizationmentioning
confidence: 99%